Oil retention and its mass distribution within a R290 room air conditioner using miscible or partially miscible oils. (March 2020) - Wu, Jianhua; Chen, Zhenhua; Chen, Rui; Du, Yanjun; Duan, Jvyuan; Li, Xiaoyang
Highlights: Oil mass distribution within a R290 RAC using various oils was measured. The oil retention was only 1.9–8.2 g, 0.79%–3.9% of the total oil quantity. The oil mass was nearly proportional to the refrigerant mass in heat exchangers. The miscibility effect of the R290/PAG mixture was mild on this R290 RAC. Viscosity grade of oil was the most critical parameter for oil mass in gas line. Abstract: At present, a variety of lubricating oils are available for R290 room air conditioners (RACs). R290 is highly miscible with mineral oils (MOs), while it is partially miscible with some alkylene oils (PAGs). In this paper, the oil retention behavior of a 1.5 HP R290 RAC with two miscible MOs and two partially miscible PAGs was studied. Firstly, the OCR of a R290 rotary compressor with PAG VG60 or MO VG100 was measured in compressor performance test platform, and it was 0.66–0.88%. Then the oil retention and its mass distribution within the RAC using PAG VG60 or MO VG100 were measured by Remove and Weight Technique (RWT) and Mix and Sample Technique (MST). And then, the oil retention when using PAG VG40 or MO VG56 was measured by RWT for further comparison. Results showed that the oil retention was 1.9–8.2 g, only 0.79%–3.9% of the total oil quantity. The oil mass in heat exchangers was nearly proportional to the local refrigerant mass, while that in gas line was greatly affected by the viscosity grade of oil. It was verified that the miscibility effect of the R290/PAG mixture was mild on this R290 RAC, and the viscosity grade of oil was the most critical parameter for the oil retention in the gas line.